2019
DOI: 10.3390/ijerph16245105
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Attitude Change After a Single-Day Manager Training Addressing Mental Health at the Workplace

Abstract: Mental health problems have become one of the most common causes of incapacity for work, and engender high costs to society. Especially managerial behavior was found to have a great impact on employees' well-being. In order to support those in leading positions in dealing with their own, as well as their employees', psychological stress factors, we conducted a specific manager training. At the same time, we wanted to find out about the training's short-and long-term effects. Participants were asked to give inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…The present study showed changes in knowledge-based stigma in the intervention group measured using MAKS three months after training. This is in line with the findings published by Schwarz and colleagues [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study showed changes in knowledge-based stigma in the intervention group measured using MAKS three months after training. This is in line with the findings published by Schwarz and colleagues [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, the values obtained by the SoDi were near to the minimum, corresponding to a floor effect without the relevant possibility for improvement. The values corresponded to those found by Schwarz and colleagues [ 47 ]. As with their study, a possible rationale lies in social desirability, furthered by the social working culture of the company.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The BCT ''information about consequences'' (health, emotional, or social and environmental) was identified in 10 articles primarily relating to raising awareness about the issues of mental ill-health, suicide, and/or posttraumatic stress disorder (PTSD); the impact of stigma; and the importance of social support, communication, and help-seeking (Gullestrup et al, 2011;King et al, 2018King et al, , 2023Milner, Law, et al, 2018;Milner et al, 2019;Ross, Caton, Mathieu, et al, 2020;Sage et al, 2016;Sayers et al, 2019;Tynan et al, 2018). ''Information about antecedents''-defined as the emotions that precede or predict a behavior-was identified in all included articles primarily relating to improving knowledge about risk and protective factors and signs of stress, mental ill-health, PTSD, and/or suicidal behavior (Gast et al, 2022;Gullestrup et al, 2011;King et al, 2018King et al, , 2023Milner, Law, et al, 2018;Milner et al, 2019;Ross, Caton, Mathieu, et al, 2020;Sage et al, 2016;Sayers et al, 2019;Schwarz et al, 2019;Tynan et al, 2018). The BCT ''social support'' related to providing information and/or facilitating discussion groups on where to seek-help; how to refer someone in distress; how to structure conversations around mental health and manage employees in distress; telephone support or counseling; encouraging people to seek or offer help; and providing psychological counseling to workers; was identified in 11 articles (Gast et al, 2022;Gullestrup et al, 2011;King et al, 2018King et al, , 2023Milner, Law, et al, 2018;Milner et al, 2019;Ross, Caton, Mathieu, et al, 2020;Sayers et al, 2019;Schwarz et al, 2019;Tynan et al, 2018).…”
Section: Intervention Functions and Bctsmentioning
confidence: 99%
“…Interestingly, manager training need not be long or intensive to show impact. Schwarz and colleagues ( 2019 ) found that a 1-day manager training can have a long-term improvement in areas such as stigma-related knowledge of mental health, and Milligan-Saville et al ( 2017 ) showed that a 4-h training not only had a longer-term impact on managers’ confidence and behavior dealing with mental health, but also led to a reduction in sickness absence.…”
Section: Workplace Mental Health and Suicide Prevention Trainingmentioning
confidence: 99%